2007
DOI: 10.1080/00103620601094031
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur Mineralization and Carbon, Nitrogen, and Sulphur Relationships in Some Alfisols of India

Abstract: The amount of sulphur (S), nitrogen (N), and organic carbon (C) in different layers of soils from some Alfisols varied considerably with location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
1
0
1
Order By: Relevance
“…For total sulphur (S) content, the study showed that there was no significant difference (P<0.05). This result opposed the previous study that showed total S decreased with depth due to the decline in organic C content (Dolui & Pradhan, 2007). The weathering process of the topsoil layer may reduce the total S content t that is mobile in the soil and exists in the form of organic matter (Prasad & Shihav, 2018).…”
Section: Resultscontrasting
confidence: 90%
“…For total sulphur (S) content, the study showed that there was no significant difference (P<0.05). This result opposed the previous study that showed total S decreased with depth due to the decline in organic C content (Dolui & Pradhan, 2007). The weathering process of the topsoil layer may reduce the total S content t that is mobile in the soil and exists in the form of organic matter (Prasad & Shihav, 2018).…”
Section: Resultscontrasting
confidence: 90%
“…~ 339 ~ The data obtained for total sulphur during analysis was in line to that obtained by Lande et al (1977) [12] as total sulphur in saline soils ranged from 425.7 to 1057 ppm, with an average of 840.4 ppm, demonstrating that total sulphur in saline soils was much higher than in normal soils, Douli and Bandyopadhyay (1983) [13] found that total sulphur content ranged from 368 to 2206 ppm, with a mean of 1011 ppm, Bhatnagar et al (2003) [14] reported that the total sulphur in surface soil of Vertisols ranged from 798 to 987 mg kg -1 with mean value of 892 mg kg -1 and total S content in soils of the Osmanabad district of Maharashtra varied between 300-2500 mg kg -1 with a mean value of 1654 mg kg -1 in vertisols, according to Narale et al (2017) [15] .…”
Section: Status Of Total Sulphur In North Saurashtra Agro-climatic Zo...supporting
confidence: 85%